Electrospun materials and their allied applications - Inamuddin; Boddula, Rajender; Ahamed, Mohd Imran; Asiri, Abdullah M. (John Wiley & Sons, Inc., 2020)
"The aim of this book is to explore the history, fundamentals, manufacturing processes, optimization parameters, and applications of electrospun materials. The book includes various types of electrospun materials such as antimicrobial, smart, bioinspired systems. It focuses on the many application areas for electrospun materials such as energy storage and harvesting, catalysis, biomedical including gene delivery and tissue engineering, separation, adsorption and water treatment technologies, packaging. The book emphasizes the enhanced sustainable properties of electrospun materials, with the challenges and future developments being discussed in detail. The chapters are written by top-class researchers and experts from throughout the world"-- Provided by publisher
Keywords: Fibers.; Fibers -- Industrial applications.; Polymers.; Polymers -- Industrial applications.; Electrospinning.; elektronické knihy; electronic books